Aerobic exercise-induced lactate production: a novel opportunity for remodeling the tumor microenvironment - Zhou, Xin; Jiang, Jinliang; Liu, Jingjing; Wang, Qinglu; Luo, Ying; Wu, Liping (Frontiers in Genetics, 2025)
Cancer, as one of the most deadly and burdensome diseases in the world today, causes irreversible damage to the body. However, due to the ineffective suppression of the inflammatory environment within tumors, identifying new therapeutic targets for cancer treatment has become an urgent issue. Recent studies have shown that lactate, a key product of glycolysis and exercise, is closely related to tumor development. Under normal conditions, lactate regulates various biological functions and can influence immune suppression, thereby interfering with tumor progression. Due to the Warburg effect, lactate levels in the tumor microenvironment (TME) are maintained at high levels. High levels of lactate can further induce the activation of an emerging post-translational modification—lactylation, which enhances the expression of relevant signaling pathways, including JAK-STAT and PI3K/Akt/mTOR. This, in turn, suppresses the body’s immune surveillance function and drives tumor progression through epigenetic-metabolic interactions. At the same time, aerobic exercise, as an important intervention for cancer, can enhance anti-inflammatory capacity by secreting muscle factors such as iris protein and tumor suppressor M, and it can also increase the infiltration of immune cells, including CD8+ T cells, improving tumor-killing abilities. Based on this, regular aerobic exercise can accelerate the clearance rate of lactate in the body, enhance lactate metabolism, reduce lactate concentration in the TME, and alleviate immune suppression. Therefore, this review explores the mechanisms behind the abnormal elevation of lactate in tumor cells and the occurrence of lactylation, proposing that aerobic exercise can intervene in the tumor process by inhibiting lactylation. The aim is to explore the interaction between aerobic exercise-induced lactylation modification and the tumor microenvironment, identify new therapeutic targets for solid tumors, and provide new ideas for their treatment.